Comparison of Broiler Chicken Behavioral Response in Differing Closed House Length throughout the Dry Season - Winda Virdya Sitorus; Dwi Sunarti; Teysar Adi Sarjana (Jurnal Peternakan Integratif, 2019)
This study aims at comparing the behavioral response of broiler chickens maintainedat different closed house length in the dry season. 600 broiler chickens with an average weightof 41.30 ± 2.68 g and two closed house units, each with a length of 60 m and 120 m having acapacity of 11,000 and 22,000 were used. Heat production is represented through eating,walking, and stretching behaviors. This research observed drinking and resting behaviors of thechickens. This is descriptive research conducted in the starter period (14 days old) of thechickens. The results show that the resting and stretching behaviors of chickens residing in the120 m closed house are higher than those in the 60 m closed house; no difference is observedin drinking behaviors. The average frequency and duration of walking and eating of chickensresiding in the 120 m closed house are lower than those in the 60 m closed house indicatingthat broilers reduce the frequency and duration of walking and eating. The findings show thatchickens raised in longer cages will show behavioral responses representing an increase of heatloss and a reduction of heat production.Keywords: broiler chicken behavior, heat loss, heat production, dry season, closed house.